Utilization of the Dorkoro Classic Custom Youtube Channel as a Means of Information for Custom Motorcycle Lovers in Pekanbaru - Fitra, Brahma (LPPM Institut Studi Islam Sunan Doe, 2024)
The purpose of this study is to find out the use of the Dorkoro Classic Custom YouTube Chanel as a means of information for custom motorbike lovers in Pekanbaru and to find out the fulfillment of the audience's information needs for Dorkoro Classic Custom YouTube Chanel as a means of information for custom motorbike lovers in Pekanbaru. The research method used in this study is to use qualitative research, with data collection techniques, namely by observation, interviews and documentation. Judging from the nature of this research, it is a descriptive research, namely research that provides a clear and detailed description of the main research issues. The results of the discussion of this study are Utilization of the Dorkoro Classic Custom YouTube Channel as a medium of information, promotion, and additional income and Fulfillment of the audience's information needs for the Dorkoro Classic Custom YouTube Channel as an Information Facility for Custom Motorcycle Lovers in Pekanbaru. In terms of information and knowledge, the Dorkoro Classic Custom YouTube Chanel does indeed provide quite the maximum service.